Assessment of Sex from the Anthropometric Measurements of the Foot in Ogbomosho North Local Government Area - Akinloye, S. Ayobami; Oyewo, O. Oluwatoyin; Saka, O. Stephen; Enye, L. Anderson; Olajide, O. Modupeoluwa (International Journal of Human Anatomy, 2020)
The aim of this physical anthropometric study is to determine sex by foot measurements. Dismembered human remains are frequently found in cases of mass disasters and criminal mutilation. It is therefore of interest to use foot dimensions for the determination of sex (gender) of an individual in order to assist in establishing personal identity. Another application of anthropometrical measurement is in ergonomics which is the design of working space and the development of industrialized products such as furnishing, cars, tools, shoe designing etc. 500 adult subjects(250 males, 250 females)aged 18-50 years without any foot disability within Ogbomosho North Local Government, Oyo State were randomly selected for the study. The males had an average foot length about 1cm greater than females and foot breadth in males was about 1cm greater as compared to females. Difference in foot length and foot breadth in males and females of the population was highly significant. With the statistical analysis, any foot with length lesser than 26cm and breadth lesser than 11cm can be suggested to be that of a female while any foot with length greater than 26cm and breadth greater than 11cm can be suggested to be that of a male. Therefore, 26cm can be taken as the cut-off point for foot length and 11cm as the cut-off point for foot breadth in this locality.
Keywords: ergonomics; anthropometry; right foot length; right foot breadth; left foot length; left foot breadth.